A study to assess symptom profile and break through infections among health care workers post covid vaccination at tertiary care health facility - Vishal Malhotra; Simmi Oberoi; Ravinder Khaira; Rajinder S Balgir; Balpreet Kaur; Sakshi Kaura (Wolters Kluwer Medknow Publications, 2022)
Introduction: Breakthrough infections in fully vaccinated persons pose a major challenge to the ongoing vaccine campaign against SARS-CoV-2 globally. Objectives: To investigate the occurrence of breakthrough infections and the association of Covid symptoms with the vaccination status of health care workers (HCWs). Material and Methods: Done in Government Medical College, Patiala among Covid-positive HCWs who have received one or both doses of Covid vaccine, using pretested semi-structured validated Proforma and telephonic interview from April 1, 2021 to June 15, 2021. Results: Among 3388 HCWs, 115 vaccinated HCWs (1st or 2nd dose) became Covid positive. Among vaccinated Covid positive HCWs, 54 received the first dose and 61 both doses. Breakthrough infections (≥14 days post 2nd dose) occurred in 4.6% (47 of 1021) HCWs. The vaccine is significantly protective as shown by an odds ratio of 0.27; thus, vaccinated HCWs are 73% less likely to get Covid infection as compared to non-vaccinated HCWs. There was no statistically significant difference between symptom profiles of cases whether they took one or both doses of vaccine, except headache. Only tiredness and headache were reported significantly higher in the unvaccinated group in comparison to vaccinated HCWs. Conclusion; Research is needed on tracking the immune response and viral genomic sequence of samples of vaccinated Covid-positive HCWs to have constant vigilance on remerging new strains of the SARS-CoV-2.